Studi Komparatif Pemberitaan Konflik Kemanusiaan Palestina-Israel (Republika Online dan CNN Indonesia) - Ahmad Fauzi; Dina Fianamalia (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The conflict between Palestine and Israel has been going on for over seven decades, which began well before 1948. This long-standing conflict has resulted in a significant loss of life. Consequently, this conflict has drawn international attention, including Indonesia. Each media outlet has a distinct perspective on reporting the conflict, especially when the media outlets' affiliations differ, which leads to a diversity of news framing. This study aims to investigate and compare how Republika Online and CNN Indonesia frame news of humanitarian conflicts between Palestine and Israel. The news period under study spans from October 7 to 15, 2023. This research employs a qualitative approach using Zhongdang Pan and Gerald M. Kosicki’s framing analysis model, grounded in Peter L. Berger and Thomas Luckmann’s theory of social construction of reality. This study found that Republika Online tends to frame the Israel-Palestine conflict in a way that favors the Palestinian side. Conversely, CNN Indonesia exhibits a more diverse framing approach, with a tendency towards pro-Palestinian coverage compared to neutral and pro-Israeli reporting. These findings suggest that the media's background does not be the sole factor influencing the framing of news content. Individual journalists and their professional orientations also play a significant role in shaping news narratives.